Microwave-assisted synthesis of ZnSn(OH)6used for photodegradation of methyl orange - Nitjawan Plubphon (2018)
Copyright © 2017 American Scientific Publishers All rights reserved. Cubic-like perovskite zinc hydroxystannate (ZHS, ZnSn(OH) 6 or ZnSnO 3 · 3H 2 O) was successfully synthesized in the alkaline solutions under a microwave radiation. This method has an advantage for the synthesis of homogeneous powder due to the nucleation and subsequent crystalline growth at low temperature. The as-synthesized ZHS was characterized by different techniques to determine phase, morphology, crystallite size, functional groups, surface area and optical properties. The appropriate/best sample was used for photocatalytic application. UV-visible analysis of the best crystalline ZHS indicated a n exponential decreasing of photonic absorption attenuated through the solid with 3.68 eV energy gap, and the ZHS photocatalyst can degrade methyl orange under UV illumination for 96% within 240 min.